2014
DOI: 10.1158/1055-9965.epi-14-0537
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Risk of Colorectal Cancer in the Iowa Women's Health Study

Abstract: Background: Colorectal cancer, the third most common cancer in the United States, has a natural history that usually encompasses several decades. Dietary components have been implicated in the etiology of colorectal cancer, perhaps through their effect on inflammation.Methods: We examined the ability of the dietary inflammatory index (DII) to predict colorectal cancer in the Iowa Women's Health Study. The DII was computed based on dietary intake assessed by a 121-item food frequency questionnaire in this cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
155
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 150 publications
(177 citation statements)
references
References 42 publications
(52 reference statements)
20
155
2
Order By: Relevance
“…CRC risk was increased by 51 and 65 % when participants in the third and the fourth DII quartile, respectively, were compared with those in the first quartile. Similar results were previously observed in the Iowa Women's Health Study, although the CRC risk, in this cohort, was only increased by 20 % (Shivappa et al 2014a). Despite the limited evidence on the relationship between overall inflammatory effects of diet and CRC risk, other epidemiological studies have reported comparable associations between CRC risk and antiinflammatory foods (e.g., fruits and vegetables) (World Research Cancer Fund and American Institute for Cancer Research 2007), nutrients (e.g., fiber, selenium, and folate) (van Duijnhoven et al 2009), and other bioactive compounds (e.g., flavonoids) (Zamora-Ros et al 2013b).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…CRC risk was increased by 51 and 65 % when participants in the third and the fourth DII quartile, respectively, were compared with those in the first quartile. Similar results were previously observed in the Iowa Women's Health Study, although the CRC risk, in this cohort, was only increased by 20 % (Shivappa et al 2014a). Despite the limited evidence on the relationship between overall inflammatory effects of diet and CRC risk, other epidemiological studies have reported comparable associations between CRC risk and antiinflammatory foods (e.g., fruits and vegetables) (World Research Cancer Fund and American Institute for Cancer Research 2007), nutrients (e.g., fiber, selenium, and folate) (van Duijnhoven et al 2009), and other bioactive compounds (e.g., flavonoids) (Zamora-Ros et al 2013b).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, higher circulating CRP and cytokine levels (inflammatory markers) have been associated with increased CRC risk in case-control studies, but in cohort studies, these associations have been less conclusive Our results suggest that the association of DII score with colon cancer risk could be stronger than with rectal cancer risk, but the interaction was not statistically significant. In other epidemiological studies, similar associations were reported for colon and rectal cancer risks with DII score (Shivappa et al 2014a), and intakes of fruits and vegetables, fiber, and flavonoids (World Research Cancer Fund and American Institute for Cancer Research 2007; Zamora- Ros et al 2013b;Murphy et al 2012). However, for circulating CRP levels, significant associations were observed only for colon cancer risk (Aleksandrova et al 2010;Wu et al 2013).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Dietary Inflammatory Index (DII) is a dietary tool developed to measure the inflammatory potential of individual's diet (Cavicchia et al 2009;Shivappa et al 2014a). DII has been shown to be predictive of levels of various inflammatory markers (Cavicchia et al 2009;Shivappa et al 2014b;Shivappa et al 2015b).…”
Section: Introductionmentioning
confidence: 99%